2022
DOI: 10.3311/ppci.19065
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on Mortar Removal Methods and their Influence on Recycled Aggregate Properties

Abstract: The adhered mortar attached to recycled aggregate (RA) is one of the main causes of weakening the mechanical properties and durability performance of recycled aggregate concrete (RAC). Therefore, in order to improve the performance of RA and RAC, several methods have been proposed to remove the adhered mortar in RA. However, knowing the adhered mortar content is as important as removing it. This is because concrete mix designs considering the amount of adhered mortar have been proposed and better strength, dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…The density of SCC using 19 mm MAS was 0.6% to 2% higher than that of SCC with The SCC mixture with a w/b ratio of 0.39 increased the density by 0.6% when the MAS was increased from 9.5 mm to 19 mm, whereas the mixture with a w/b ratio of 0.45 increased by 2% for a given MAS. Smaller RAs have a higher adhered mortar content than larger RAs, resulting in lower density and higher water absorption [14]. Hence, SCC mixtures made from RA with large MAS exhibit higher density than mixtures with smaller MAS, which is consistent with the results reported in [24].…”
Section: Hardened Properties 321 Densitysupporting
confidence: 87%
See 3 more Smart Citations
“…The density of SCC using 19 mm MAS was 0.6% to 2% higher than that of SCC with The SCC mixture with a w/b ratio of 0.39 increased the density by 0.6% when the MAS was increased from 9.5 mm to 19 mm, whereas the mixture with a w/b ratio of 0.45 increased by 2% for a given MAS. Smaller RAs have a higher adhered mortar content than larger RAs, resulting in lower density and higher water absorption [14]. Hence, SCC mixtures made from RA with large MAS exhibit higher density than mixtures with smaller MAS, which is consistent with the results reported in [24].…”
Section: Hardened Properties 321 Densitysupporting
confidence: 87%
“…The adhered mortar absorbs mixing water and deteriorates the workability. In our previous study [14], it was reported that the smaller the aggregate size, the higher the adhered mortar content. Therefore, the workability of the SCC with 9.5 mm MAS is inferior to that of the SCC with 19 mm MAS.…”
Section: Specimen Preparation and Test Methodsmentioning
confidence: 87%
See 2 more Smart Citations